ChemInform Abstract: Oxidative Dimerization of Isoflavones: Synthesis of Kudzuisoflavone A and Related Compounds. Issue 17 (4th April 2013) - Deodhar, Mandar; Wood, Kasey; Black, David StClair; Kumar, Naresh
Abstract A facile method for the oxidative dimerization of methoxy‐substituted isoflavones is presented.